2013 Physics Education Research Conference Proceedings 2014
DOI: 10.1119/perc.2013.pr.021
|View full text |Cite
|
Sign up to set email alerts
|

Computational Thinking for Physics: Programming Models of Physics Phenomenon in Elementary School

Abstract: Abstract.Computational thinking, an approach to problem solving, is a key practice of science education rarely integrated into instruction in an authentic way. A second key practice, creating models of physical phenomenon, has been recognized as an important strategy for facilitating students' deeper understandings of both science concepts and the practices of science. We are creating an interdisciplinary computational thinking curriculum for grades 4-6 that combines the development of computational thinking w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 6 publications
0
18
0
2
Order By: Relevance
“…Hence, there is a real gap in the research field on the implementation of computational thinking among students. Dwyer et al (2014) found that using computational thinking and programming as a method of physics learning can help students to master the learning. Additionally, exposing students to computational-based learning can help students in mastering science content such as Kinematics and Ecology and computational thinking effectively (Basu et al, 2014).…”
mentioning
confidence: 99%
“…Hence, there is a real gap in the research field on the implementation of computational thinking among students. Dwyer et al (2014) found that using computational thinking and programming as a method of physics learning can help students to master the learning. Additionally, exposing students to computational-based learning can help students in mastering science content such as Kinematics and Ecology and computational thinking effectively (Basu et al, 2014).…”
mentioning
confidence: 99%
“…Using a drawing activity based on the Marching Orders activity by CS Unplugged, we found that fourth graders recognized the need for but struggled to produce specific instructions [10]. We also tested prior knowledge for our algorithms learning progression strand.…”
Section: My Thesis Research Is Made Up Of Four Componentsmentioning
confidence: 98%
“…We created a theoretical set of learning progressions based on existing curricula by CSTA and used focus groups to test the lower anchor points [6,10]. Using a drawing activity based on the Marching Orders activity by CS Unplugged, we found that fourth graders recognized the need for but struggled to produce specific instructions [10].…”
Section: My Thesis Research Is Made Up Of Four Componentsmentioning
confidence: 99%
“…Instead, they suggested, "just as proficiency in basic language arts helps us to effectively communicate and proficiency in basic math helps us to successfully quantitate, proficiency in computational thinking helps us systematically and efficiently process information and tasks" Computational Thinking in Teacher Education (Fletcher & Lu,p. These computational thinking concepts can be implemented in K-12 classrooms through digital storytelling, data collection and analysis, and scientific investigations (Lee, Martin & Apone, 2014), creating games (Howland & Good, 2015;Lee et al, 2014;, educational robotics (Atmatzidou & Demetriadis, 2014), physics (Dwyer, Boe, Hill, Franklin, & Harlow, 2013), visual programming languages like Scratch or other interactive media Calao, Moreno-Leon, Correa, & Robles, 2015), and even through maker movements (Rode et al, 2015). This effort to lay foundations of CT needs to start early on in students' K-12 experience before they learn programming languages (Fletcher & Lu).…”
Section: Computational Thinking In K-12mentioning
confidence: 99%